Method for improving IV characteristic of YBCO nanowire

By adopting controllable heat treatment and voltage-driven enhancement methods in YBCO nanowires, the IV characteristics are optimized, and the problem of poor IV characteristics of YBCO nanowires is solved, which significantly improves its superconducting performance and light detection performance, providing strong support for the application of SNSPD.

CN119584846AActive Publication Date: 2025-03-07UNIV OF ELECTRONICS SCI & TECH OF CHINA
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN202411677603.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-03-07
Estimated Expiration
2044-11-22

AI Technical Summary

Technical Problem

After YBCO nanowires are processed into narrow nanowires, the IV characteristics are poor, the hysteresis is weak or even completely disappears, and the existing processes are difficult to implement, which affects its application in SNSPD.

Method used

Controllable heat treatment and voltage drive enhancement methods are adopted to optimize the IV characteristics of the nanowires by diffusion of oxygen atoms and charging carrier density regulation in YBCO nanowires. Specific steps include growing YBCO film and amorphous protective layer on the substrate, preparing nanowire devices, and enhancing its IV characteristics through plasma-enhanced atomic layer deposition and voltage-driven enhancement processing.

Benefits of technology

It significantly improves the critical current density, hysteresis window and voltage jump of YBCO nanowires, enhances the stability of its superconducting state, improves the light detection performance, and improves the sensitivity and time resolution of the detector.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119584846A_ABST
    Figure CN119584846A_ABST
Patent Text Reader

Abstract

The invention provides a method for improving IV characteristics of YBCO nanowires, and belongs to the technical field of single photon detection. According to the method, the IV characteristic of the YBCO nanowire is improved through the combination of controllable heat treatment and voltage driving enhancement treatment, the YBCO nanowire obtained through the method can increase the critical current Ic and the critical current density Jc, the Jc can be improved to 1.86 MA.cm <-2 >, the hysteresis window can be widened, the superconducting state is more stable, and sharp voltage jump is achieved; besides, the nanowire device with degraded superconducting performance can be changed into an obvious lag state from an original magnetic flux flow state, and the superconducting characteristic is improved, so that the optical detection capability is recovered, and the detection sensitivity, the time resolution, the environmental stability and other performances of the detector are greatly improved. And a powerful support is provided for the realization and application expansion of the SNSPD based on the YBCO nanowire in the future.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of single-photon detection, and in particular relates to a method for improving IV characteristics of YBCO nanowires. Background Art

[0002] Superconducting nanowire single photon detectors (SNSPDs) that can operate at temperatures above liquid helium are a hot topic at home and abroad. High-temperature SNSPDs greatly reduce system operating costs and bring great hope for change in the application of superconducting technology, so they have extremely wide potential applicability. c =92K), large-area epitaxial growth, shorter electron-phonon relaxation time, etc. 7-x (YBCO) stands out among various high-temperature superconducting materials as a leading candidate for practical SNSPD applications.

[0003] In the preparation, evaluation and practical application of SNSPD, the current-voltage (IV) characteristic is one of the most basic and important characteristics of the device. SNSPD generates a voltage pulse when absorbing a single photon, which is a metastable state generated under current bias. This metastable state is essential for the operation of the detector, and is manifested as a hysteretic IV characteristic, which is the result of the competition between the current-induced Joule self-heating and the electron cooling process of the nanowire in the resistive state. It determines whether the nanowire device can generate a measurable voltage signal after absorbing a single photon, which is crucial to the application of SNSPD. For the IV characteristic, the hysteresis window is an important condition for representing the nanowire device's ability to detect light. Under the condition of the same nanowire size, the critical current (I c ) is larger, which means the critical current density (J c ) is larger, the better the quality of the nanowire; the sharper the voltage jump, the greater the resistance of the nanowire when it becomes a resistive state, the more obvious the voltage signal, and the larger the amplitude of the light detection signal; the larger the hysteresis window, the more stable the superconducting state of the nanowire. Therefore, for SNSPD, the research focus is on preparing YBCO nanowires with higher critical current density, sharper voltage jump and better hysteresis window.

[0004] YBCO thin films are sensitive and their superconducting properties are easily degraded. After being processed into very narrow nanowires, the IV characteristics are poor, and the hysteresis is weak or even disappears completely. Some researchers (Andersson E, Arpaia R, Trabaldo E, et al. Fabrication and electrical transport characterization of high quality underdoped YBa2Cu3O7-δ nanowires [J]. Superconductor Science and Technology, 2020, 33 (6): 064002.) have successfully prepared narrow nanowires (200nm) using underdoped YBCO thin films, giving them hysteresis IV characteristics, but there are great challenges in terms of doping uniformity, repeatability of hysteresis phenomena, and long-term stability. Because the underdoping process is difficult to achieve in a controllable manner, this method is more suitable as a technical means to study specific physical phenomena (such as quantum phase slip, nonlinear transport, etc.), rather than an ideal process for large-scale application. At the same time, some researchers (Baghdadi R, Arpaia R, Charpentier S, et al. Fabricating nanogaps in YBa2Cu3O7-δ for hybrid proximity-based Josephson junctions [J]. Physical Review Applied, 2015, 4 (1): 014022.) successfully improved the IV characteristics of YBCO nanowires by in-situ ozone treatment, turning resistive nanowires into superconducting ones, but IV hysteresis was still not obtained. Therefore, how to improve the IV characteristics of YBCO nanowire devices in order to realize SNSPD based on YBCO nanowires has become a key issue to be solved urgently. Summary of the invention

[0005] In view of the problems existing in the background technology, the purpose of the present invention is to provide a method for improving the IV characteristics of YBCO nanowires. The method combines controllable heat treatment and voltage drive enhancement method to obtain nanowires with better hysteresis IV characteristics, so that the nanowires maintain a more stable superconducting state, which can greatly improve the potential light detection performance of the device.

[0006] To achieve the above object, the technical solution of the present invention is as follows:

[0007] A method for improving the IV characteristics of YBCO nanowires, comprising the following steps:

[0008] Step 1: growing a YBCO film on the substrate surface, and then in-situ growing an amorphous YBCO protective layer on the surface of the YBCO film to prevent the YBCO film from being degraded by contact with the atmospheric environment during subsequent processing;

[0009] Step 2: attaching an electrode pattern mask to the amorphous YBCO protective layer, and then using electron beam evaporation to prepare a metal electrode. After the electrode preparation is completed, remove the mask, and then use plasma enhanced atomic layer deposition to grow a dense aluminum oxide protective layer;

[0010] Step 3: Prepare YBCO microwire devices by using ultraviolet lithography combined with low-temperature inductively coupled plasma reactive ion etching to locate the area where the nanowires are to be made;

[0011] Step 4: Prepare the desired nanowire device by using electron beam lithography combined with low-temperature inductively coupled plasma reactive ion etching;

[0012] Step 5: placing the nanowire device obtained in step 4 in a chamber of a plasma enhanced atomic layer deposition system, performing a heat treatment under a specific working atmosphere, and cooling it naturally after the reaction is completed, and then taking it out after cooling it to room temperature;

[0013] Step 6: Place the nanowire device obtained in step 5 on a temperature-controlled DC probe station, and use a voltage-driven enhancement method to process the nanowire. The processing process is: at a low temperature of 4K, increase the external electric field control voltage value in a certain voltage step until the critical voltage threshold, and perform an IV hysteresis curve test at each external electric field control voltage value. After the test, the required YBCO nanowire with good IV characteristics can be obtained.

[0014] Further, in step 1, the growth substrate may be a strontium titanate, magnesium oxide or lanthanum aluminate substrate;

[0015] Furthermore, in step 1, the thickness of the YBCO film is not less than 5 nm; the thickness of the amorphous YBCO protective layer is not less than 8 nm; and the growth method is preferably a DC magnetron sputtering method.

[0016] Furthermore, in step 2, the vacuum degree of the electron beam evaporation system chamber is less than 5×10 -6 mbar, the evaporation rate is

[0017] Furthermore, in step 3 and step 4, the sample stage temperature of low-temperature inductively coupled plasma reactive ion etching is -20°C--10°C, the etching gas is Ar / Cl2 mixed etching gas, the ICP power is 800-1200W, the RF power is 80-120W, and the etching pressure is 1mTorr.

[0018] Furthermore, the specific working atmosphere in step 5 is preferably pure Ar, N2, pure oxygen or air; the heat treatment temperature is 150-200°C, and the treatment time is not less than 1 hour.

[0019] Furthermore, in step 6, the critical voltage threshold is positively correlated with the size of the YBCO nanowires. The thinner the nanowires, the smaller the critical voltage threshold; preferably, it is 8-20V.

[0020] Furthermore, the voltage step value is preferably 1-3V.

[0021] The mechanism of the present invention is:

[0022] Controlled heat treatment can promote the diffusion of oxygen atoms in YBCO nanowires, thereby making the oxygen doping distribution more uniform. Its role is reflected in the following two aspects: on the one hand, it effectively reduces the defect density of superconducting nanowires, weakens the local inhomogeneity caused by defects, and thus reduces the formation of local hot spots; at the same time, the uniform oxygen distribution makes the superconducting current more evenly distributed on the nanowires, reduces the local weakening of the current density caused by factors such as poor contact, and significantly reduces the randomness of the critical current. On the other hand, after oxygen diffuses to the edge area of ​​the nanowire, it can repair the edge oxygen loss problem caused by etching, expand the effective superconducting wire width, and thus optimize the IV characteristics of the nanowire.

[0023] Voltage-driven enhancement can generate a strong electric field inside the material, induce the migration of oxygen ions or oxygen vacancies, and achieve local regulation of oxygen doping concentration, thereby changing the charge carrier density of YBCO and adjusting its superconducting properties; high electric fields can enhance the stability of the dynamic transition process from the superconducting state to the normal state, and reduce the non-uniform transport phenomenon caused by defects or local uneven distribution of oxygen. At the same time, the combined action of thermal effects and high voltages introduces nonlinear dynamic effects, which helps to eliminate non-ideal responses in weakly connected areas and improve the repeatability of measurements, playing a key role in optimizing the IV characteristics of nanowires.

[0024] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0025] The method of the present invention is used to improve the IV characteristics of YBCO nanowires by combining controllable heat treatment and voltage-driven enhancement treatment. The YBCO nanowires obtained by the method of the present invention can not only increase the critical current (I c ), improve the critical current density J c , J c Can be increased to 1.86MA·cm -2It can also widen the hysteresis window, making the superconducting state more stable and having a sharp voltage jump; in addition, it can also make the nanowire device with degraded superconducting performance change from the original flux flow state to an obvious hysteresis state, improve the superconducting properties, and thus restore the ability of light detection, greatly improving the detection sensitivity, time resolution and environmental stability of the detector, and providing strong support for the future realization and application expansion of SNSPD based on YBCO nanowires. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a comparison chart of the IV characteristics of YBCO nanowires with a line width of 400 nm obtained in Example 1 and Comparative Examples 1 and 2.

[0027] Figure 2 This is a comparison chart of the IV characteristics of YBCO nanowires with a line width of 600 nm obtained in Example 1 and Comparative Examples 1 and 2.

[0028] Figure 3 YBCO nanowires I obtained in Example 1 and Comparative Example 1 and Comparative Example 2 c Statistical comparison chart.

[0029] Figure 4 Schematic diagram of IV characteristics of YBCO nanowires damaged by high voltage obtained in Comparative Example 3.

[0030] Figure 5 This is the optical display image of the YBCO meandering nanowires obtained in Example 2.

[0031] Figure 6 It is a comparison chart of the IV characteristics of YBCO meandering nanowires obtained in Example 2 and Comparative Examples 4 and 5. DETAILED DESCRIPTION

[0032] In order to make the objectives, technical solutions and advantages of the present invention more clear, the present invention is further described in detail below in conjunction with the implementation modes and the accompanying drawings.

[0033] Example 1

[0034] A method for improving the IV characteristics of YBCO nanowires, comprising the following steps:

[0035] Step 1: Select a strontium titanate substrate and clean it. Use DC magnetron sputtering to grow a 6nm thick YBCO film on the substrate surface. The chamber is filled with a mixed gas of O2:Ar=1:3, the gas pressure is 30Pa, the sputtering power is 125W, and the chamber temperature is 802℃. After the film growth is completed, wait for the chamber to cool to room temperature, and then grow a 10nm thick amorphous YBCO protective layer on the YBCO film with the same gas conditions and sputtering power.

[0036] Step 2: Attach the electrode pattern stainless steel mask to the amorphous YBCO protective layer, and then use electron beam evaporation to prepare the metal electrode (Ag / Au: 20nm / 20nm). The vacuum degree of the cavity is less than 5×10 -6 mbar, the evaporation rate is

[0037] After the electrode preparation is completed, the mask is removed, and then a 10nm dense aluminum oxide protective layer is grown on the entire device surface using plasma enhanced atomic layer deposition to further isolate the nanowires from damage by air;

[0038] Step 3: UV photolithography of the sample obtained in step 2: first clean the surface of the sample obtained in step 2 (acetone megasonic for 5 minutes, isopropyl alcohol for 5 minutes, rinse with isopropyl alcohol, and blow dry with N2); then place it on a 110°C hot plate for pre-baking for 1 minute; spin-coat AZ5214 photoresist (6000rmp, 60s); bake the glue on a 110°C hot plate for 1 minute; after UV exposure, develop it with ZX238 for 45s to locate the micron area of ​​the nanowire to be made connected to the electrode channel; use inductively coupled plasma reactive ion etching on the sample after UV photolithography to obtain a 30μm micron wire device: use a mixed etching gas (Ar / Cl2: 18 / 2sccm), an ICP power of 1000W, an RF power of 100W, an etching pressure of 1mTorr, and maintain the sample stage temperature at -20°C to prevent thermal damage caused by the etching process; the degumming process is 10min of acetone soaking, 20min of megasonic, isopropyl alcohol rinse and then blow dry with N2;

[0039] Step 4: Electron beam lithography of the sample obtained in step 3: First, clean the surface of the sample obtained in step 3, and then place it on a 180°C hot plate for pre-baking for 1 minute; spin-coat ZEP-520A electron beam photoresist (7000 rpm, 60 seconds), and bake the glue on a 180°C hot plate for 3 minutes; spin-coat conductive carbon glue (4000 rpm, 60 seconds), and bake the glue on a 110°C hot plate for 2 minutes; at an acceleration voltage of 20 kV and an exposure dose of 30 uC / cm 2The nanowires were patterned by electron beam exposure under the condition of ; the conductive carbon glue was rinsed with deionized water to remove it, and it was developed with ZED-N50 developer at room temperature for 3 minutes after being blown dry with N2, and then immersed in isopropanol for 15 seconds, rinsed with deionized water and blown dry with a nitrogen gun; the samples after electron beam lithography were subjected to inductively coupled plasma reactive ion etching to obtain single nanowire devices with line widths of 400nm, 600nm, 800nm, 1μm and 2μm; the degumming process was ultraviolet light treatment for 5min, acetone soaking for 10min, megasonic for 20min, isopropanol rinsing and blown dry with N2; all nanowire devices were placed in a temperature-controlled DC probe station, and IV hysteresis curve tests were performed at a low temperature of 4K, with a maximum limiting voltage of 4V;

[0040] Step 5: Place the nanowire device obtained in step 4 in the chamber of a plasma enhanced atomic layer deposition system and perform heat treatment in a N2 atmosphere at a temperature of 200°C for 1 hour. After the reaction is completed, the cooling rate is about 27°C / min, and the nanowire device is taken out after cooling to room temperature.

[0041] Step 6: Place the nanowire device obtained in step 5 into a temperature-controlled DC probe station, and use a voltage-driven enhancement method to process the nanowire. The processing process is as follows: at a low temperature of 4K, the initial external electric field control voltage is 4V, and the external electric field control voltage value is increased in 2V voltage steps until it reaches 8V. An IV hysteresis curve test is performed at each external electric field control voltage value. After the test, the desired YBCO nanowire with good IV characteristics can be obtained.

[0042] Example 2

[0043] YBCO meandering nanowires were prepared according to the steps of Example 1, except that step 4 was adjusted as follows: the nanowire size structure was a meandering nanowire with a line width of 400 nm.

[0044] The optical microscope image of the YBCO meandering nanowires prepared in this example is shown in Figure 5 As shown in the figure, it can be seen that the width of the nanowires is uniform.

[0045] Comparative Example 1

[0046] YBCO nanowires were prepared according to the steps of Example 1, except that Step 5 and Step 6 were omitted and the remaining steps remained unchanged.

[0047] Comparative Example 2

[0048] YBCO nanowires were prepared according to the steps of Example 1, except that step 6 was omitted and the remaining steps remained unchanged.

[0049] Comparative Example 3

[0050] YBCO nanowires were prepared according to the steps of Example 1, except that step 6 was adjusted as follows: an IV hysteresis curve test was performed at a low temperature of 4K, and the external electric field regulation voltage was gradually increased to 22V in steps of 2V.

[0051] Comparative Example 4

[0052] YBCO meandering nanowires were prepared according to the steps of Example 2, except that Step 5 and Step 6 were omitted and the remaining steps remained unchanged.

[0053] Comparative Example 5

[0054] YBCO meandering nanowires were prepared according to the steps of Example 2, except that step 6 was omitted and the remaining steps remained unchanged.

[0055] The comparison diagrams of IV characteristics of YBCO nanowires with line widths of 400 nm and 600 nm obtained in Example 1 and Comparative Example 1 and Comparative Example 2 are shown as follows: Figure 1 and Figure 2 As shown. Figure 1 It can be seen that the 400nm nanowire device prepared in Comparative Example 1 has no IV hysteresis (magnetic flux flow state), and the nanowire device prepared in Comparative Example 2 becomes an obvious hysteresis state. c The IV characteristics in Example 1 are further optimized. c Increases significantly, and the hysteresis window becomes wider. Figure 2 As can be seen, the 600nm nanowire device I c The hysteresis window becomes wider and the voltage jump becomes larger.

[0056] Figure 3 YBCO nanowires I obtained in Example 1 and Comparative Example 1 and Comparative Example 2 c Statistical comparison chart. Figure 3 As shown, the I c Statistical analysis shows that nanowire devices I c and J c Therefore, it can be confirmed that the IV characteristics of the nanowire device prepared by the present invention are significantly improved after being processed in step 5 and step 6.

[0057] When the external test voltage increases to 22V, the IV characteristics of the YBCO nanowires damaged by high voltage are shown in the figure. Figure 4 As shown in the figure, it can be seen that due to the excessively high voltage, the nanowire device is instantly damaged to an insulating state; therefore, the external test voltage threshold of the present invention needs to be within a specific range to be improved, otherwise the excessively high voltage will cause irreversible damage to the nanowire.

[0058] The comparison of IV characteristics of YBCO meandering nanowires with a line width of 400 nm obtained in Example 2, Comparative Example 4 and Comparative Example 5 is shown in FIG. Figure 6 As shown; the IV characteristics of the meandering nanowire prepared in Comparative Example 4 have no hysteresis and are close to a resistive state. Comparative Example 5 becomes an obvious superconducting state after heating treatment, but still has no IV hysteresis; the meandering nanowire prepared in Example 2 has an obvious IV hysteresis window, I c It significantly increases to 164 μA, and the voltage jump is sharp; therefore, the present invention has obvious and universal effects on improving the superconducting performance and optimizing the IV characteristics of YBCO nanowires.

[0059] The above description is only a specific implementation mode of the present invention. Any feature disclosed in this specification, unless otherwise stated, can be replaced by other alternative features that are equivalent or have similar purposes; all the disclosed features, or all the steps in the methods or processes, except for mutually exclusive features and / or steps, can be combined in any way.

Claims

1. A method for improving the IV characteristics of YBCO nanowires, characterized in that: The following steps are involved: Step 1: growing a YBCO film on the substrate surface, and then in-situ growing an amorphous YBCO protective layer on the surface of the YBCO film to prevent the YBCO film from being degraded by contact with the atmospheric environment during subsequent processing; Step 2: attaching an electrode pattern mask to the amorphous YBCO protective layer, and then using electron beam evaporation to prepare a metal electrode. After the electrode preparation is completed, remove the mask, and then use plasma enhanced atomic layer deposition to grow an aluminum oxide protective layer; Step 3: Prepare YBCO microwires by using ultraviolet lithography combined with low-temperature inductively coupled plasma reactive ion etching; Step 4: Prepare YBCO nanowires by electron beam lithography combined with low temperature inductively coupled plasma reactive ion etching; Step 5: placing the YBCO nanowires obtained in step 4 in a chamber of a plasma enhanced atomic layer deposition system, performing heat treatment under a specific working atmosphere, and cooling them naturally after the reaction is completed, and then taking them out after cooling to room temperature; Step 6: Place the YBCO nanowire obtained in step 5 on a temperature-controlled DC probe station, and use a voltage-driven enhancement method to process the nanowire. The processing process is: at a low temperature of 4K, increase the external electric field control voltage value in a certain voltage step until the critical voltage threshold, and perform an IV hysteresis curve test at each external electric field control voltage value. After the test, the desired YBCO nanowire with good IV characteristics can be obtained.

2. The method for improving IV characteristics of YBCO nanowires according to claim 1, characterized in that: In step 1, the growth substrate is a strontium titanate, magnesium oxide or lanthanum aluminate substrate; 3. The method for improving IV characteristics of YBCO nanowires according to claim 1, characterized in that: In step 1, the thickness of the YBCO film is not less than 5 nm; the thickness of the amorphous YBCO protective layer is not less than 8 nm; and the growth method is a DC magnetron sputtering method.

4. The method for improving IV characteristics of YBCO nanowires according to claim 1, characterized in that: In step 2, the vacuum degree of the electron beam evaporation system chamber is less than 5×10 -6 mbar, the evaporation rate is 5. The method for improving IV characteristics of YBCO nanowires according to claim 1, characterized in that: In step 3 and step 4, the sample stage temperature of low-temperature inductively coupled plasma reactive ion etching is -20°C--10°C, the etching gas is Ar / Cl2 mixed etching gas, the ICP power is 800-1200W, the RF power is 80-120W, and the etching pressure is 1mTorr.

6. The method for improving IV characteristics of YBCO nanowires according to claim 1, characterized in that: The specific working atmosphere in step 5 is pure Ar, N2, pure oxygen or air; the heat treatment temperature is 150-200°C, and the treatment time is not less than 1 hour.

7. The method for improving IV characteristics of YBCO nanowires according to claim 1, characterized in that: In step 6, the critical voltage threshold is positively correlated with the size of the YBCO nanowire. The thinner the nanowire, the smaller the critical voltage threshold.

8. The method for improving IV characteristics of YBCO nanowires according to claim 7, characterized in that: The critical voltage threshold is 8-20V.

9. The method for improving IV characteristics of YBCO nanowires according to claim 1, characterized in that: The voltage step value is 1-3V.

Citation Information

Patent Citations

  • Electrical, mechanical, computing, and / or other devices formed of extremely low resistance materials

    CN105264680A

  • Preparation method of superconducting nanowire single-photon detector

    CN111947794A

  • Gated superconducting single photon detection device and method

    CN113008392A

  • Preparation method of on-chip SNSPD speed regulation and control device

    CN116113170A

  • Preparation method of YBCO nanowire

    CN118591267A